Sustainable Digital Marketing Strategy for Long-Term Growth of MSMEs - Risdwiyanto, Andriya; Sulaeman, Moh. Muklis; Rachman, Andy (ADMAN: Journal of Contemporary Administration and Management, 2023)
In recent years, the advancement of digital technology has brought fundamental changes in consumer behavior regarding information seeking, product comparison, and purchasing. Small and Medium Enterprises (MSMEs) need to adapt to these trends to remain competitive and thrive. This research aims to examine sustainable digital marketing strategies for the long-term growth of MSMEs. The approach involves a qualitative analysis of literature, intending to obtain a comprehensive understanding of the subject from 2018 to 2023. The study's findings indicate that, in the face of increasingly fierce competition in the digital era, MSMEs must adopt sustainable digital marketing strategies to ensure the long-term growth of their businesses. Market and audience understanding, continuity in branding, SEO optimization, social media utilization, content marketing, data analysis, email marketing, and investment in learning and innovation are key elements in achieving these goals.